Provenance of the Hinglaj formation in southern Balochistan - Sheikh, Khawar Sohail; Khan, Abdul Salam; Farooqui, Mohammad Ahmad; Yaqoob, Khurram (Journal of Himalayan Earth Sciences, 2005)
Miocene-Pliocene Hinglaj Formation is widely exposed in southern Balochistan. For current study of provenance investigation, samples have been collected from Nal and Bela area. The percentages of the frame work grains have been deduced from point counting using the standard method. All the encountered frame work constituents were counted and intergranular fine grained quartz was treated as matrix. The point counting results represent the volume of the original grains. The petrographic analyses of mostly medium to coarse grained, moderately to well sorted samples indicate that the maximum percentages of frame-work grains are upto 88 % monocrystalline quartz, 15 % polycrystalline quartz, 13 % chert, 8 % plagioclase feldspar, 3 % potash feldspar, 24 % sedimentary rock fragments, 17 % volcanic rock fragments, 2 % biotite, 3 % muscovite, 2 % heavy minerals including zircon, hornblende, sphene, rutile, epidote, 17 % opaque minerals, 8 % shell fragments, 35 % algae fragments and 17 % microfossils. The point counting data, when plotted in the QFL, QmPK, QmFLt, and QpLvLs ternary diagrams indicate Recycled Orogen Provenance. On the basis of the petrographic results, geological histoly of the region since early Miocene lasting to the present day and interpretation of the previous workers, it can be concluded with reasonable confidence that the Hinglaj Formation has a mixed provenance. The major detritus was derived from the• Himalayan Crystalline Belt and minor volcanic content was incorporated from Chagai Magmatic Arc.